A Tentative Proposal for Machine Assisted Human Translation (MAHT) – Tool-Specific General Text Typology - Feder, Marcin (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The aim of the present article is to contend the widespread but largely unfounded claim that MAHT tools (popularly known as translator ’s work-benches) are best suited for translating so-called technical texts. The article calls for establishing a separate MAHT tool-specific text typology by pre-senting what are – in the author ’s opinion – the most important features characteristic of an MAHT-suitable text. It transpires that it is difficult to simply relate this particular type of text to any of the existing classifications of translation-related or general text typologies (such as those advocated by, for example, Hatim & Mason 1990; Reiß 1983; Snell-Hornby 1988 or Kussmaul 1997) since the existing methodologies do not take MAHT-specif¬ic attributes into account. Therefore, the present article calls for an empi¬rical, corpus-based study that would help establish the relation between the proposed underlying features and actual text types as described elsewhere.